PENGARUH PENDEKATAN KONTEKSTUAL BERBASIS ETNOMATEMATIKA BUDAYA SUNDA TERHADAP KEMAMPUAN PEMAHAMAN DAN DISPOSISI MATEMATIS SISWA PADA MATERI PERSEGIPANJANG - Nugraha, Trisna; Maulana, M.; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2017)
Human life always involves mathematics, so needed mastery of mathematical understanding ability, and mathematical disposition (MUA-MD) since early age. Innovative mathematic learning through Sundanese culture ethnomatematics (SCE)-based contextual approach is chosen as a solution in improving MUA-MD. This study aims to determine the improvement of students MUA-MD that learn through SCE-based contextual approach, and conventional learning, knowing differences in improvement between SCE-based contextual approach, and conventional learning, knowing the positive relationship between MUA and MD. This research used pretest-posttest control group design with samples of grade V SDN Cibeureum 3, and SDN LicinÂ in Sumedang. Conclusions of this research are: 1) SCE-based contextual, and conventional approach can improve MUA-MD significantly, 2) SCE-based contextual approach is significantly better to improving goals than conventional approach, 3) There is positive relationship between mathematical understanding ability, and mathematical disposition.